Derrida and feminism : recasting the question of woman - Feder, Ellen K.; Rawlinson, Mary C.; Zakin, Emily (Routledge, 1997)
The first-ever compilation of articles that highlights the intersection of Derridean and feminist theories--a work that represents the extensive and diverse response feminist theorists have had to Derrida, particularly to the issues of gender, identity, and the construction of the subject.